Effect of Carbonization Temperature, Particle Size, and Binder Type on the Quality and CO Emissions of Oil Palm Shell Bio-Briquettes - Novrida Harpah Hasibuan; Isra Suryati; Rahmi Karolina; Orisa Sativana Megawati; Trie Nova Marito Sitanggang; Yerica Magdalena Silaen; Sarah Patumona Manalu (Talenta Publisher, 2026)
Bio briquettes from palm kernel shells have the potential to replace fossil fuels as an alternative energy source. However, their quality is largely determined by the characteristics of the raw materials and the type of binder. This study aims to analyze the effect of binder type (starch and molasses), carbonization temperature, charcoal particle size, and binder concentration on briquette quality. The parameters tested included moisture content, ash content, compressive strength, calorific value, and CO2 emissions, as specified in the Indonesian National Standard (SNI). Briquettes were produced through carbonization, mixing, molding, and drying, then tested by proximate analysis, compression testing, calorimetry, and gas emissions analysis. The results indicated that binder type affects moisture content, ash content, and strength, but does not impact calorific value. Briquettes with molasses produced the lowest moisture content of 1.1%, namely in samples with 350°C, 100 mesh, 20% molasses. The lowest ash content and highest sample strength were obtained in samples with starch binder (350°C, 60 mesh, 20% starch), namely 2.2% and 39.91 Kg/cm2. The sample with the highest calorific value was 6561.49 Cal/g (400°C, 60 mesh, 20% molasses). Interestingly, the binder type did not significantly affect the calorific value; particle size was the dominant factor. In terms of emissions, molasses produced lower CO2 (812 ppm) than starch, at 400°C, 60 mesh particles, and a molasses concentration of 15%. This study confirms that the choice of binder significantly influences the physical and mechanical properties of bio briquettes, but does not significantly affect their calorific value. These findings provide important guidance for optimizing palm oil waste-based briquette formulations to produce efficient, environmentally friendly, renewable energy.